Land, Liberties, and Lordship in a Late Medieval Countryside : Agrarian Structures and Change in the Duchy of Wrocław - Hoffmann, Richard C. (2016)
Richard C. Hoffman's monumental study of rural life in medieval eastern Europe focuses on one region, the Duchy of Wroclaw, from the twelfth to sixteenth centuries. The duchy is in many ways a microcosm of medieval European society, and thus Hoffman's analysis addresses issues central to a broader understanding of a vanished society. His analysis of the records of the Duchy of Wroclaw challenges the western stereotypes of east central Europe that have been imposed on its medieval past by modern nationalisms. Honorable Mention, Wallace K. Ferguson Prize of the Canadian Historical Association.